Endometrial Epithelial Cell Apoptosis Is Inhibited by a ciR8073-miR181a-Neurotensis Pathway during Embryo Implantation - Lei Zhang; Xiaorui Liu; Sicheng Che; Jiuzeng Cui; Xingna Ma; Xiaopeng An; Binyun Cao; Yuxuan Song (Elsevier, 2019)
Development of the receptive endometrium (RE) from the pre-receptive endometrium (PE) is essential for embryo implantation, but its molecular mechanisms have not been fully understood. In this study, lncRNA-miRNA-mRNA and circRNA-miRNA-mRNA networks were constructed to explore the functions of potential competing endogenous RNAs (ceRNA) during the development of RE in dairy goats. We observed that circRNA8073 (ciR8073) decreased the levels of miR-181a by acting as a miRNA sponge. This effect indirectly increased the expression of neurotensin in endometrial epithelial cells (EECs). Neurotensin then inhibited EEC apoptosis by increasing the expression of BCL-2/BAX in favor of BCL-2 via the MAPK pathway and also induced increased expression of leukemia-inhibitory factor, cyclo-oxygenase 2, vascular endothelial growth factor A, and homeobox A10. We have thus identified a ciR8073-miR181a-neurotensin pathway in the endometrium of dairy goats. Through this pathway, ciR8073 functions as a ceRNA that sequesters miR-181a, thereby protecting neurotensin transcripts from miR-181a-mediated suppression in EECs. Keywords: receptive endometrium, ceRNA, ciR8073-miR181a-NTS, endometrial epithelial cells, EECs, dairy goats